Transcatheter mitral and tricuspid interventions—the bigger picture: valvular disease as part of heart failure - Curio, Jonathan; Beneduce, Alessandro; Giannini, Francesco (Frontiers in Cardiovascular Medicine, 2023)
The prevalence of mitral (MR) and tricuspid regurgitation (TR), especially, in heart failure (HF) populations is high. However, the distinct role of atrioventricular valve diseases in HF, whether they are merely indicators of disease status or rather independent contributors in a vicious disease cycle, still is not fully understood. Especially, tricuspid regurgitation (TR) for decades was considered as an innocent bystander, subsequent to other heart or lung pathologies, thus, not needing dedicated treatment. Recent increasing awareness towards the role of atrioventricular valve diseases has revealed that MR and TR are, in fact, independent predictors of outcome in HF, thus, warranting attention in the HF treatment algorithm. This awareness arose, especially, as with minimally invasive transcatheter solutions new treatment options, also for patients considered at increased surgical risk, have been developed. However, outcomes of such transcatheter treatments have, in parts, been sub-optimal, likely influenced by the status of the concomitant HF disease. Thus, this review aims to summarize data on the current understanding regarding the role of MR and TR in HF, how HF impacts outcomes of transcatheter MR and TR interventions, and how the understanding of this relationship might help to identify patients that benefit most from these therapies, proven to be life-saving in properly selected candidates.